Safeguarding our Atmosphere: Legal Measures and Health (London Journal of Research In Science: Natural and Formal, 2024)
The depletion of the ozone layer, a critical shield protecting the Earth from harmful ultraviolet (UV) radiotion, has become a global environ- mental concern. This paper highlights the legal dimensions surrounding Ozone-depleting substances (ODS), their impact on the Ozone layer, and the subsequent risk on human health specially regarding skin cancer and blindness. As countries navigate international agreements, domestic reg- ulations, and enforcement mechanisms, the intricate interplay between legal frameworks and health implication of ozone layer depletion comes to the forefront.The paper also highlights specific cases of illegal trade in ozone deplet- ing substances provided by parities to the Montreal Protocol, examining statistics provided by parties to the Montreal Protocol. China emerges as a major producer of contraband ODS, while countries such as Bulgaria, Lithuania, Poland, and France report numerous cases. Analyzing these cases provides insights into the effectiveness of legal frameworks and enforcement agencies.The paper concludes with a set of recommendations designed to spread control and enforcement against the illegal trade of ozone-depleting substances. These recommendations encompass multiple aspects, in- cluding production monitoring, customs collaboration, mutual verifica- tion, cross-border agreements, public-private partnerships, international cooperation, detection equipment, global regulatory standards, resource allocation, public awareness campaigns, alternative substance develop- ment, and controlling the trade at its source. By applying these recom- mendations and enhancing enforcement measures, we aim to protect the ozone layer and create a healthier and safer world for future generations and achieving the sustainable developments goals.
Keywords: Solanaceae; Solanum boldoense Dunal & A.DC; Steroidal compounds.; Ozone-depleting substances; Illegal trade; Montreal Protocol; Environ- mental protection; Ozone layers; Skin cancer; blindness.